DEXMEDETOMIDINE PREMEDICATION WITH KETAMINE AND PROPOFOL DURING BURNS DEBRIDEMENT AND DRESSINGS - Kiran, Suprabhat; Rai, Prashant; VK, Badhe; RR, Kunkulol (International Journal of Clinical and Biomedical Research, 2017)
Background: Burn patients undergo frequent extensive burn debridement and painful dressing changes. Ketamine and Propofol are the most common anesthetic used along with Opioids and Benzodiazepines in burns dressings. Studies have shown that concomitant use of Dexmedetomidine with Propofol and Ketamine. Objectives: To study the effects of Dexmedetomidine as premedication with Ketamine and Propofol as sole anesthetic agents during burns debridement and dressing. Materials and methods: Total 60 Patients of scheduled for elective burn debridement and dressings at P.R.H. Loni admitted in the wards were enrolled for the study. Patients satisfying the following eligibility criteria were selected and grouped those who received Ketamine and Propofol (Group B) with and without Dexmedetomidine (Group A) and both the groups were assessed to find out difference in the dose requirement, haemodynamic variables and recovery time (using Ramsay Sedation scale). Results: The haemodynamic parameters like heart rate, systolic and diastolic Blood pressure was significantly higher in Group A as compared to Group B. The recovery time in Group A was 12.9 mins as compared to 9.5 mins in Group B. It was observed that dose requirement of Ketamine (228.8±21.9) and Propofol (263.2 ± 22.5) was significantly more in Group A as compared to Group B (101.1±20.3 and 120.8±22.4 respectively).Conclusion: Dexmedetomidine (1μg/kg IM dose) is a good anaesthetic adjuvant that decreases the requirement of Propofol and Ketamine during burns debridement and dressings, maintains stable intraoperative haemodynamics and also has an excellent recovery profile. Key words: Dexmedetomidine; Haemodynamic Changes; Ketamine; Propofol; Recovery Time.